The Expression of MMP-2 Following Immobilization and High-Intensity Running in Plantaris Muscle Fiber in Rats - Eli Carmeli; Tal Gal Haimovitch (The Scientific World Journal)
The effect of 2-week, high-intensity running and a 2-week immobilization on muscle fiber type composition of the plantaris muscle from 18 female, 6-month-old Wistar rats (running, n = 6; immobilization, n = 6; sedentary control, n = 6) was bio- and histochemically investigated. The high-intensity treadmill running began with 20 min (32 m/min, 0% gradient, 75% VO2 max), up to 50 min/day. Right hind limbs were immobilized by an external fixation procedure for 13 days. Muscle mass of the plantaris muscle in the immobilized groups was reduced by 16% in comparison with the sedentary control group. High-intensity running and immobilization increased both mRNA and protein levels of matrix metalloproteinase type 2 (MMP-2) in plantaris. Running and immobilization decreased the percentages of transverse sectional area of fast-twitch glycolytic (FG) type IIb fibers, running increased relative cross-sectional area of fast-twitch oxidative glycolytic (FOG) type IIa muscle fibers, whereas immobilization increased relative cross-sectional area of slow-twitch oxidative (SO) muscle fibers (type I). Our results suggest that both high-intensity running and immobilization are enough to induce overwhelming changes in plantaris.